COMPARISON OF INFORMATIONAL CONTENT OF THE METHOD OF DYNAMIC FOCUSING AND DIFFERENTIAL PHASE METHOD OF DEFINITION OF THE SURFACES ROUGHNESS - Стельмах, О.; Софронов, О.; Чернишова, С. (Science-based technologies, 2012)
In this work is considered differential-phase method and method of autofocusing, which are used on differential-phase laser scanning profilograph-profilometer (DFLSPP) and microscope «MICROSCAN» correspondently. Also is considered experimental comparison of defining of 3D micro- and nano-geometrical surface conditions and standardized roughness parameters of surface with the help of those methods.